Cosmopolis $1 (BVolume 2s - Bourget, Paul, 1852-1935 (Salt Lake City, UT : Project Gutenberg, 2003)
"Cosmopolis $1 (BVolume 2" by Paul Bourget is a novel likely written during the late 19th century. The book centers around Julien Dorsenne, a novelist who becomes entangled in a complex web of personal relationships and social intrigues, particularly involving Countess Steno and Boleslas Gorka, as he grapples with themes of love, jealousy, and moral dilemmas. The opening of the novel introduces us to Dorsenne's troubled state of mind as he reflects on his interactions with Gorka, who has recently returned to Rome in a tumultuous emotional state. Dorsenne is pulled into a dilemma that questions his integrity and loyalty, especially regarding his relationships with the women involved. He observes the dynamics of their circle, filled with suspicion and unspoken tension, as he attempts to decipher the source of anonymous letters that have stirred jealousy and anxiety. As he prepares to confront the impending confrontation at a dinner hosted by Countess Steno, the atmosphere is charged with the potential for conflict, reflecting the intricate moral landscapes Bourget illustrates throughout the narrative. (This is an automatically generated summary.)s
Release date is 2003-04-01
This etext was produced by David Widger
Keywords: French fiction -- Translations into English